Assessment of the modern state of the innovative management system of commercial organizations in agriculture (Economics and region, 2024)
For commercial organizations, innovation and innovative activities are the basis for providing competitive advantages. Agriculture is the most important sector of the national economy. By providing the population with food and raw materials for industry, it has an important influence on the development of the entire economy of the country, including rural areas. Agricultural production mainly shapes the level of employment and income of the rural population, affects demographic processes, settlement and development of rural areas. World experience proves that there is simply no alternative to innovative development in a knowledge-based economy. The creation, implementation and widespread distribution of new products, services, and technological processes are becoming the main factors in the growth of production, employment and investment. In modern conditions of market transformations and the transition of agricultural science to innovative principles, the choice of a strategic line and methodology for the practical implementation of investment projects with elements of innovative development is of great importance. The creation of favorable institutional conditions and the necessary motivational environment for the development of agricultural science requires the formation of an effective system of parity of economic interests of the creators of innovative products and consumers of innovative products. The task of creating innovative products that allow obtaining competitive advantages for local production is of particular relevance from the point of view of innovative activities in the agro-industrial complex, since the introduction of innovative measures, solutions and a coordination complex in the activities of agricultural producers will increase the competitiveness of agro-industrial products and its local markets, as well as provide its stable position in the world markets. In modern times, both new technologies and new management methods should be actively included in the experience of commercial organizations working in the field of agriculture. Value added in agriculture should be considered as an innovative development. The wide application of scientific and technological achievements is the most effective form of ensuring the sustainable development of commercial organizations working in the field of agriculture, and scientific and technological progress itself is determined by the possibilities of an innovative way of developing agricultural production.
Keywords: agriculture; innovation; innovation management; commercial organizations; food security